2018
DOI: 10.1177/0956797617737385
|View full text |Cite
|
Sign up to set email alerts
|

Attractive Serial Dependence in the Absence of an Explicit Task

Abstract: Attractive serial dependence refers to an adaptive change in the representation of sensory information, whereby a current stimulus appears to be similar to a previous one. The nature of this phenomenon is controversial, however, as serial dependence could arise from biased perceptual representations or from biased traces of working memory representation at a decisional stage. Here, we demonstrated a neural signature of serial dependence in numerosity perception emerging early in the visual processing stream ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
135
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(158 citation statements)
references
References 32 publications
20
135
3
Order By: Relevance
“…Our findings are compatible with recent decisional accounts of serial dependence (e.g. Bliss et al (2017); Fritsche et al (2017), but see Cicchini et al (2017); Fornaciai and Park (2018)) that propose that not perception itself, but rather later decisional stages bias behavior towards previously seen stimuli. Specifically, the ideal observer framework proposed here capitalizes on the stability of the visual world to make the best possible decisions, integrating sensory observations across time while weighting each piece of evidence by its uncertainty.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are compatible with recent decisional accounts of serial dependence (e.g. Bliss et al (2017); Fritsche et al (2017), but see Cicchini et al (2017); Fornaciai and Park (2018)) that propose that not perception itself, but rather later decisional stages bias behavior towards previously seen stimuli. Specifically, the ideal observer framework proposed here capitalizes on the stability of the visual world to make the best possible decisions, integrating sensory observations across time while weighting each piece of evidence by its uncertainty.…”
Section: Discussionsupporting
confidence: 92%
“…Until now, the processing stage at which serial dependence occurs has remained unclear. While some studies have suggested a perceptual stage 3,11,22,31,32 , others have provided evidence for a memory-or decision-related process 6,20,33,34 . These seemingly contradictory results can be reconciled by assuming that serial dependence operates on multiple stages during object processing, as recently proposed 7 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to repulsive adaptation, recent studies have found that perceptual decisions about stimulus features can be attracted towards stimuli encountered in the recent past -a phenomenon termed attractive serial dependence . Like repulsive adaptation, attractive serial dependence has now been reported for a large variety of visual features, such as orientation (Cicchini et al, 2017;Czoschke et al, 2019;Fritsche et al, 2017), numerosity (Cicchini et al, 2014;Corbett et al, 2011;Fornaciai and Park, 2018) and spatial location (Bliss et al, 2017;Manassi et al, 2018;Papadimitriou et al, 2016). This phenomenon may represent a (Bayes-)optimal strategy of decoding the sensory information into a perceptual decision (Cicchini et al, 2018;van Bergen and Jehee, 2019).…”
Section: Introductionmentioning
confidence: 94%